2005
DOI: 10.1152/jn.00319.2005
|View full text |Cite
|
Sign up to set email alerts
|

Disparity-Tuning Characteristics of Neuronal Responses to Dynamic Random-Dot Stereograms in Macaque Visual Area V4

Abstract: Stereo processing begins in the striate cortex and involves several extrastriate visual areas. We quantitatively analyzed the disparity-tuning characteristics of neurons in area V4 of awake, fixating monkeys. Approximately half of the analyzed V4 cells were tuned for horizontal binocular disparities embedded in dynamic random-dot stereograms (RDSs). Their response preferences were strongly biased for crossed disparities. To characterize the disparity-tuning profile, we fitted a Gabor function to the disparity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
58
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 71 publications
(37 reference statements)
11
58
1
Order By: Relevance
“…Recent studies have shown the existence of disparity-selective neurons in the ventral visual pathway (Janssen et al, 1999;Uka et al, 2000;Connor, 2001, 2005;Watanabe et al, 2002;Tanabe et al, 2005). We have now shown the functional relevance of disparity-selective IT neurons in a depth discrimination task.…”
Section: The Role Of Disparity-selective Neurons In the Ventral Visuamentioning
confidence: 51%
See 3 more Smart Citations
“…Recent studies have shown the existence of disparity-selective neurons in the ventral visual pathway (Janssen et al, 1999;Uka et al, 2000;Connor, 2001, 2005;Watanabe et al, 2002;Tanabe et al, 2005). We have now shown the functional relevance of disparity-selective IT neurons in a depth discrimination task.…”
Section: The Role Of Disparity-selective Neurons In the Ventral Visuamentioning
confidence: 51%
“…The distinction between the ventral and dorsal visual pathways (Ungerleider and Mishkin, 1982) cannot be based on the existence of disparity-selective neurons, because both pathways contain neurons sensitive for binocular disparity (Maunsell and Van Essen, 1983;Roy et al, 1992;Eifuku and Wurtz, 1999;Janssen et al, 1999;Taira et al, 2000;Uka et al, 2000;Connor, 2001, 2005;Watanabe et al, 2002;DeAngelis and Uka, 2003;Tanabe et al, 2005). The mere existence of these neurons does not reveal the functional role that these pathways play (Parker and Newsome, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of exhaustively testing every possible variable of the task, we artificially boosted the activity of V4 neurons with electrical microstimulation in a separate set of sessions. We were able to selectively activate near-preferring or far-preferring neurons because V4 neurons are clustered according to its preferred disparity (see Materials and Methods, above) (Watanabe et al, 2002;Tanabe et al, 2005). If the monkeys based their decision on the representation of disparity in V4, we expected frequent decisions toward the preference of the stimulated site.…”
Section: Microstimulation Of V4 Neurons During the Fine Disparity Dismentioning
confidence: 99%